Music and Inspiration - Harvey, Jonathan 1939-2012 (London Faber & Faber, 1999)
In Music and Inspiration, one of Britain's foremost composers, Jonathan Harvey, draws on the writings of a wide range of composers in an effort to understand and define what inspiration really is. His choice of material is expansive, aiming to chart what it is that composers from different backgrounds have in common, and how the concept of inspiration persists within otherwise very different musical cultures.Inspiration is commonly believed to be the product of a single moment, but the truth is more complex. Tchaikovsky wrote that "those who imagine that a creative artist can -- through the medium of his art -- express his feelings at the moment that he is moved, make the greatest mistake". Composers have drawn inspiration from a wide variety of sources: Debussy's muse was the majesty of nature, while Stravinsky admitted that the desire for praise comprised a great part of his musical creativity, and Brahms believed that inspiration was no less than a gift directly from God. Harvey discusses potential sources, such as philosophy, the unconscious, and external events, and examines the links between them, all the while building a rich and multifaceted understanding of what inspiration means for a composer.
Keywords: Composing